Examining the protective influence of posttraumatic growth on interpersonal suicide risk factors in a 6-week longitudinal study - Yasdiman, Meryem Betul; Townsend, Ellen; Blackie, Laura E. R. (Frontiers in Psychology, 2022)
Research has found an inverse relationship between posttraumatic growth (PTG) and suicidal ideation in military and community samples that holds when controlling for other suicide risk factors. However, further research is needed into the underlying mechanisms to clarify how PTG protects against the formation of suicidal thoughts. The current two-wave longitudinal study examined whether perceiving PTG from recent adverse circumstances experienced in a national lockdown due to the COVID-19 pandemic attenuated the positive relationship of two interpersonal suicide risk factors – perceived burdensomeness (PB) and thwarted belonginess (TB) - over 6 weeks. Participants (n = 170) were recruited online from Prolific from income-deprived areas in the UK (mean age = 37.65; SD = 12.50; 53.5% female). We examined whether PTG mediated the relationship between PB at wave 1 and wave 2 while controlling for depression and anxiety in a sample of individuals at-risk for suicidal ideation. Post-hoc power analyses indicated we had insufficient power to examine the hypothesised mediation for TB. PTG did significantly and partially mediate the positive relationship between PB at wave 1 and 2. We discuss the theoretical and clinical implications that could result if future research successfully replicates these initial exploratory findings.